“This is not a rave”: An ethnography of changes in the Melbourne rave/dance party scene, 1996-2006 - Siokou, Christine (Curtin University, 2010)
This thesis explores four changes associated with the commercialisation of the Melbourne rave/dance party scene: in the location, marketing and size of rave/dance party events; in the composition of attendees; in drug-related practices; and in the ‘vibe’ or atmosphere. I argue that these changes have produced nostalgic representations about past rave forms that can also be read as claims to ‘subcultural capital’ – that is, to the possession of an ‘authentic’ rave identity.